Actionable Insights of Policy on Debt Management Units for Effective Regional Bond and Business Environment: Comparative Study of Indonesia and Mexico (Jurnal Bina Praja, 2025)
Effective public policy debt management through Debt Management Units (DMUs) is essential for regional governance and economic development. Compared with Mexico, the study focuses on actionable policy insights and the importance of DMUs in effective regional bond issuance and business environment improvement in Indonesia. The primary objective is to enhance the operational effectiveness of DMUs to facilitate successful bond issuance and improve the local business environment. The study used a qualitative research methodology to gather comprehensive insights and involved semi-structured interviews with key stakeholders, observations, and document analysis. Findings reveal that DMUs are crucial in coordinating debt strategies and managing risks; however, their effectiveness is often compromised by inadequate human resources, unclear organizational structures, and regulatory constraints. The study proposes actionable solutions, such as investing in human resource development, establishing clear Standard Operating Procedures (SOPs), and advocating for balanced regulatory reforms. These findings contribute significantly to public governance and policy by highlighting the importance of enhancing DMU performance for sustainable economic growth. The research emphasizes a multifaceted approach integrating human resource capacity, organizational clarity, and stakeholder engagement. By addressing the specific context of local government, this study provides valuable insights for policymakers and practitioners, promoting effective public finance management and fostering a favorable investment climate. The proposed recommendations aim to empower DMUs, ensuring they can fulfil their vital regional governance and economic development functions.
Keywords: Debt Management Units (DMUs); Regional Bond Issuance; Public Governance and Policy; Economic Development; Indonesia; Mexico